Phase II Trial of Cabozantinib Plus Erlotinib in Patients With Advanced Epidermal Growth Factor Receptor (EGFR)-Mutant Non-small Cell Lung Cancer With Progressive Disease on Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor Therapy: A California Cancer Consortium Phase II Trial (NCI 9303) - Reckamp, Karen L.; Frankel, Paul H.; Ruel, Nora; Mack, Philip C.; Gitlitz, Barbara J.; Li, Tianhong; Koczywas, Marianna; Gadgeel, Shirish M.; Cristea, Mihaela C.; Belani, Chandra P.; Newman, Edward M.; Gandara, David R.; et al. (Frontiers in Oncology, 2019)
Introduction: Mesenchymal epidermal transition and vascular endothelial growth factor pathways are important in mediating non-small cell lung cancer (NSCLC) tumorigenesis and epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) resistance. We hypothesized that treatment with cabozantinib plus erlotinib in EGFR mutation-positive NSCLC following progression on EGFR TKI therapy may allow tumors to overcome this resistance or restore sensitivity to therapy regardless of T790M status. Methods: Patients with advanced NSCLC, known EGFR mutation and progressive disease on an EGFR TKI immediately prior to enrollment without intervening therapy were enrolled. Patients received erlotinib 150 mg and cabozantinib 40 mg daily. The primary endpoint was evaluation of efficacy by objective response rate. Secondary endpoints included assessment of progression free survival (PFS), overall survival, change in tumor growth rate, safety and toxicity, and the evaluation of specific EGFR mutations and MET amplification in pre-treatment tissue and plasma. Results: Thirty-seven patients were enrolled at 4 centers. Four patients had partial response and 21 had stable disease. A greater than 30% increase in tumor doubling time was observed in 79% of assessable patients (27/34). Median PFS was 3.6 months for all patients. Diarrhea (32%) was the most common grade 3 adverse event; 3 patients had asymptomatic grade 4 elevation of amylase and lipase. Conclusions: Combination erlotinib and cabozantinib demonstrates anti-tumor activity in patients with EGFR mutation and progression on EGFR TKI. Further elucidation of beneficial patient subsets is warranted.